2020
DOI: 10.6007/ijarbss/v10-i11/7955
|View full text |Cite
|
Sign up to set email alerts
|

Counterproductive Work Behaviour: The Role of Work Overload and Organizational Justice Dimensions among Employees in Nigeria Private Sector Organizations

Abstract: Due to the growing employment rate, employees' voices may not be heard but they speak in salient ways especially regarding their organizational climate as regards work load and uneven distribution of organizational rewards and punishments. Considering that these circumstances elicit employees' reaction, this study explored the roles of work overload and organizational justice dimensions on counterproductive work behaviour (CWB). The design was correlation design while regression statistics was used to analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…These findings likewise strengthen the description of the theory that the higher the application of disruptive justice values felt by employees, the higher the quality of their working lives [11]. The results of the study showed that distributive justice had an overwhelmingly positive relationship with the quality of work-life perceived by employees [12].…”
Section: Introductionsupporting
confidence: 82%
“…These findings likewise strengthen the description of the theory that the higher the application of disruptive justice values felt by employees, the higher the quality of their working lives [11]. The results of the study showed that distributive justice had an overwhelmingly positive relationship with the quality of work-life perceived by employees [12].…”
Section: Introductionsupporting
confidence: 82%
“…This takes us to the second gap in the extant literature related to the mentioned earlier. Although the literature on the antecedents of sabotage behavior in the present research location (Nigeria) is highly appreciable (e.g., Akinsola & Alarape, 2020;Ezeh & Osineme, 2017;Ezeh et al, 2018;Nnaebue et al, 2020), perceived employability have not been studied in relations to negative workplace behaviors. Perceived employability is an area in management that has not been well explored, especially concerning skilled labor in manufacturing organizations.…”
Section: Introductionmentioning
confidence: 87%
“…For instance, Afghan et al (2018) found that distributive and procedural justice were significantly and negatively related to counterproductive work behavior, while Dar and Rahman (2019) found a significant negative relationship between procedural justice and workplace deviance. Also, Nnaebue et al (2020) found that the three dimensions of organizational justice (distributive, procedural, and interactional) were negatively significant with counterproductive work behavior. These studies support the notion that PJ in the organization reduces negative workplace behaviors.…”
Section: Procedural Justice As Moderator Of the Stated Relationshipmentioning
confidence: 94%
“…It is envisaged that good leader-member exchange will elicit positive psychological well-being from organizational members that will lead to a more effective and efficient organization such as; job creativity (Nwangwu et al, 2021), job satisfaction, job security and other emotional well -being (Dulebohn, Bommer, Liden, Brouer & Ferris, 2012). It may also make workers feel overloaded if they do not exchange well (Nnaebue et al, 2020). However, it has been noted that managers of banking organizations in the process of working with others, sometimes exhibit behaviors that could be seen as tyrannical, aggressive or abusive (Duffy, Ganster & Pagon, 2002;Hoobler & Brass, 2006;Hoel, Rayner & Cooper, 1999;Zellars, Tepper & Duffy, 2002).…”
Section: Introductionmentioning
confidence: 99%